"Mad Scared" versus "I Was Sad": Emotional expression and response in urban adolescent males. (June 2016) - Reigeluth, Christopher S.; Pollastri, Alisha R.; Cardemil, Esteban V.; Addis, Michael E.
Abstract: Decades of masculinity research have concluded that society places higher demands on males to adhere to norms for low emotional expression; yet, countless studies find that emotional expression is integral to well-being. Unfortunately, this contradiction places boys and men in a tenuous position as they must navigate a bombardment of societal messages about the importance of emotional stoicism and invincibility. For urban adolescents, the situation is more complicated as they encounter environmental stressors that place greater emphasis on projecting a tough façade. Thus, our primary aim was to assess to what degree dyads of close adolescent male friends from urban, low-income neighborhoods are able to engage in emotional expression and response and to explore some of the underlying mechanisms and interpersonal processes. Qualitative findings from our sample suggest that urban boys exhibit a wide range of behaviors when participating in dyadic emotional disclosure and response, including being highly emotionally expressive and supportive in the context of close male friendship.